Methodological instructions for practical classes from the discipline «Theory and methods of scientific creativity» full-time students in the specialty 274 «Motor vehicle transport» by educational and qualification level – bachelor - Nazarov, А. (Харківський національний автомобільно-дорожній університет, 2025)
Methodological instructions are intended for work on a practical task for students in the field of preparation 274 «Motor vehicle transport» of full-time study at the educational and qualification level of a bachelor in the discipline «Theory and Methods of Scientific Creativity».
Keywords: research of technical objects; measurement of technical object values; verification of research results of technical objects; дослідження технічних об’єктів; вимірювання величин технічних об’єктів; перевірка результатів досліджень технічних об’єктів; 629.01(07)